The strategic management of higher education serving students as customers for institutional growth - Kazeroony, Hamid H.; Kazeroony, Hamid H.; IG Publishing ([New York] Business Expert Press, 2012)
This book is targeted at the professionals who are interested in reorganizing or restructuring their higher education or postsecondary institutions. It examines the needs of learners in the 21st century, the rise of for-profit higher-education institutions, and the technological innovations impacting postsecondary education. It also provides examples of administrative processes and how to satisfy regulatory agencies' standards to take advantage of a particular marketing niche for attracting students. This book is organized into 13 chapters that address the changing environment of higher education and the administrative structure, challenges, and requirements for successful execution of start-up operations or changing strategies for existing institutions, as well as provide a summary of findings and additional recommendations.
1. Strategies to better serve students and grow institutions / Hamid H. Kazeroony -- 2. The changing environment of higher education / Olga Kovbasyuk and Glyn Rimmington -- 3. Organizational culture in higher education / Rana Zeine, Michael Hamlet, Patrick Blessinger, and Cheryl Boglarsky -- 4. Change process in existing institutions / David P. Bugay -- 5. The changing learners / Michael J. Sukowski -- 6. Supporting learners' activities / Robert Thorn -- 7. Online, hybrid, and face-to-face higher education / Dakin Burdick -- 8. Publishers' technologies and their impact on higher education / Virginia Jones -- 9. Administrative and academic structures: for-profit and not-for-profit / Andrew Carpenter and Craig N. Bach -- 10. Funding: student loans, scholarships, and endowments / Santa Ono, Kristi Nelson, Gisela Escoe, and Caroline Miller -- 11. Accreditation / Cyndy J. Woods-Wilson -- 12. Marketing your institution and its programs / Helena Kantanen -- 13. The 21st century higher education strategy road map / Hamid H. Kazeroony -- References -- Index.
Electronic reproduction.
Keywords: Universities and colleges -- Administration; Electronic books